Ukraine Public Finance Review - World Bank (Washington, DC, 2017)
Despite bold efforts to consolidate public finances, Ukraine’s growth potential remains undermined by a large public sector, high public debt levels and inefficient provision of critical public services. The Ukraine government faces new public spending pressures which, if realized, would reverse recent fiscal consolidation gains. In this context, the objective of this Public Finance Review (PFR) is to inform the government of Ukraine about fiscal reform options to restore sustainability of public finances while improving critical public services and improving medium-term growth prospects. The PFR offers reform options for a gradual and sustainable fiscal deficit reduction and mitigation of risks to debt sustainability through broadening the tax base, improved tax administration, and more efficient public spending. Chapter 1 provides an overview of Ukraine’s fiscal situation and key pressures to fiscal sustainability. Chapter 2 focuses on options to broaden the tax base and improve tax administration following the recent tax reform measures. Although Ukraine already collects a high share of Gross domestic product as taxes, it can improve tax compliance, broaden the tax base, and reduce the tax burden. Improving tax administration and broadening the tax base are critical to improve fiscal sustainability in the short term and to create a foundation for sustainable economic growth in the medium term. Chapter 3 focuses on options to improve the fiscal sustainability of the pensions system, which is the largest public finance expenditure item and a source of fiscal vulnerability on the expenditure side. Chapters 4, 5, 6 and 7 look at opportunities for delivering public services, specifically, education, health, social assistance and decentralization, that are more efficient, equitable and higher quality. Reforms in these areas are anchors of Ukraine’s long-term fiscal sustainability and core elements of the strategy to reduce the fiscal deficit. Analyses of expenditures in this review are structured according to functions rather than economic categories.